(untitled) (Academicia Globe: Inderscience Research, 2022)
In the course of the study, the authors improved the complexes of special preparatory exercises, taking into account the peculiarities of the phase structure of the shock actions of young taekwondo fighters, taking into account the need to use simulators. The effectiveness of the use of special preparatory exercises for teaching basic technical actions at the stage of initial training of young taekwondo sportsmen’s has been proven.